Конечные автоматы в информационных технологиях - Крывый, С.Л. (Кибернетика и системный анализ, 2011)
Наведено короткий огляд застосуваня теорiї скiнченних автоматiв у деяких сучасних галузях комп’ютерних наук i технологiй. Зокрема, розглядаються сфери застосування скiнченних автоматiв в комп’ютернiй алгебрi, мережах Петрi, бiологiї, верифiкацiї. A short review of applications of finite state automata in some modern areas of computer science and technologies is presented. In particular, fields of application of finite state automata in computer algebra, Petri nets, biology, and verification are considered.